Lido-OH, a Hydroxyl Derivative of Lidocaine, Produced a Similar Local Anesthesia Profile as Lidocaine With Reduced Systemic Toxicities - Yin, Qinqin; Zhang, Weiyi; Ke, Bowen; Liu, Jin; Zhang, Wensheng (Frontiers in Pharmacology, 2021)
Background: lidocaine is one of the most commonly used local anesthetics for the treatment of pain and arrhythmia. However, it could cause systemic toxicities when plasma concentration is raised. To reduce lidocaine’s toxicity, we designed a hydroxyl derivative of lidocaine (lido-OH), and its local anesthesia effects and systemic toxicity in vivo were quantitively investigated. Method: the effectiveness for lido-OH was studied using mouse tail nerve block, rat dorsal subcutaneous infiltration, and rat sciatic nerve block models. The systemic toxicities for lido-OH were evaluated with altered state of consciousness (ASC), arrhythmia, and death in mice. Lidocaine and saline were used as positive and negative control, respectively. The dose-effect relationships were analyzed. Results: the half effective-concentration for lido-OH were 2.1 mg/ml with 95% confident interval (CI95) 1.6–3.1 (lidocaine: 3.1 mg/ml with CI95 2.6–4.3) in tail nerve block, 8.2 mg/ml with CI95 8.0–9.4 (lidocaine: 6.9 mg/ml, CI95 6.8–7.1) in sciatic nerve block, and 5.9 mg/ml with CI95 5.8–6.0 (lidocaine: 3.1 mg/ml, CI95 2.4–4.0) in dorsal subcutaneous anesthesia, respectively. The magnitude and duration of lido-OH were similar with lidocaine. The half effective doses (ED50) of lido-OH for ACS was 45.4 mg/kg with CI95 41.6–48.3 (lidocaine: 3.1 mg/kg, CI95 1.9–2.9), for arrhythmia was 16.0 mg/kg with CI95 15.4–16.8 (lidocaine: 3.0 mg/kg, CI95 2.7–3.3), and for death was 99.4 mg/kg with CI95 75.7–124.1 (lidocaine: 23.1 mg/kg, CI95 22.8–23.4). The therapeutic index for lido-OH and lidocaine were 35.5 and 5.6, respectively. Conclusion: compared with lidocaine, lido-OH produced local anesthesia at similar potency and efficacy, but with significantly reduced systemic toxicities.